2014
DOI: 10.1152/ajpendo.00515.2013
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional islet graft histology: panoramic imaging of neural plasticity in sympathetic reinnervation of transplanted islets under the kidney capsule

Abstract: Juang J, Peng S, Kuo C, Tang S. Three-dimensional islet graft histology: panoramic imaging of neural plasticity in sympathetic reinnervation of transplanted islets under the kidney capsule. Am J Physiol Endocrinol Metab 306: E559 -E570, 2014. First published January 14, 2014; doi:10.1152/ajpendo.00515.2013.-Microscopic examination of transplanted islets in an ectopic environment provides information to evaluate islet engraftment, including revascularization and reinnervation. However, because of the dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…Avizo's noise filtering algorithms were applied for background noise reduction. Signal tracing and feature extraction were performed by the Label Field function of Avizo to estimate the tissue volume via the occupied voxels [26]. Image stacks presented in ESM Videos were recorded using the Movie Maker function of Avizo with increase in display time in association with the depth of the optical section.…”
Section: Methodsmentioning
confidence: 99%
“…Avizo's noise filtering algorithms were applied for background noise reduction. Signal tracing and feature extraction were performed by the Label Field function of Avizo to estimate the tissue volume via the occupied voxels [26]. Image stacks presented in ESM Videos were recorded using the Movie Maker function of Avizo with increase in display time in association with the depth of the optical section.…”
Section: Methodsmentioning
confidence: 99%
“…Avizo 6.2 image reconstruction software (VSG, Burlington, MA; operated with a Dell T7500 workstation), Zen software (Carl Zeiss), and LSM510 software (Carl Zeiss) were used for projection, signal segmentation, noise reduction, and analysis of confocal images. Quantitation of signal (CK19, NG2, and GFAP) density in an image stack is illustrated in (25). Briefly, to estimate density, feature extraction and image segmentation were first performed using the Label Field function in Avizo to collect voxels of lesion (or normal area) and those of CK19, NG2, or GFAP signals.…”
Section: Methodsmentioning
confidence: 99%
“…In rodents, Juang et al . (), who also used TH, demonstrated sympathetic innervation of islet grafted mouse, resembling innervation in the pancreas in situ . Slack () reported that innervation with ganglion cells and unmyelinated fibers starts at the 50 somite stage and embryonic vascularization begins at 14 days in mice.…”
Section: Discussionmentioning
confidence: 91%